Empathy is a beautiful thing: Empathy predicts imitation only for attractive others. Issue 5 (21st June 2013) - Müller, Barbara C. N.; Van Leeuwen, Matthijs L.; Van Baaren, Rick B.; Bekkering, Harold; Dijksterhuis, Ap
Abstract : Research shows that we spontaneously imitate people. Moreover, empathy predicts the degree of this non‐conscious imitation. Little is known, however, if or how this expression of empathy is influenced by stable physical characteristics of our interaction‐partners. In two studies, we tested whether attractiveness of others moderated the relation between empathy and imitation. While seeing a woman performing joystick movements, participants either imitated, or non‐imitated these movements. Results showed that the higher participants empathy score, the faster they imitated an attractive person. The level of empathy did not predict the degree of imitation of unattractive targets. The findings demonstrate that the expression of empathy through imitation can be moderated by attractiveness, thereby introducing a new dimension to the conditionality of empathy.